Factors affecting the intention to start a business of young people in Ca Mau city, Ca Mau province - Nguyen, Trần Đăng; Le, Thị Hải Đường (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The study was carried out on “Factors affecting the intention to start a business of young people in Ca Mau city, Ca Mau province” to assess the current situation of businesses and business start-ups of young people for the period of 2019-2021 and find solutions to promote young people’s intention to start a business in Ca Mau city, Ca Mau province. The study analyzed and assessed the current situation of young people starting a business in the period of 2019-2021, identifying factors affecting young people’s intention to start a business, including: (1) Standards subjective; (2) Perceived behavioral control; (3) Government policy; (4)Production capital. On that basis, the following solutions have been proposed: (1) Group ofsolutions for young people themselves: Regarding subjective standards; On perceivedbehavioral control; Regarding production capital. (2) Proposals and recommendations to thegovernment and local authorities: For the Government’s policies; For local government. Thesesolutions are to promote the intention of starting a business of young people in Ca Mau city, CaMau province in the coming time.